Fracture behavior of quenched poly(lactic acid) (eXPRESS Polymer Letters, 2011)
The effect of a quenching treatment applied on heated cast sheet extruded films of two poly(lactic acid) (PLA) commercial grades, with different optical purities, was studied. The thermal and mechanical properties of the films, as well as their fracture behavior, were assessed by differential scanning calorimetry (DSC), tensile tests, and the essential work of fracture (EWF) approach. The heating-quenching treatment causes a de-aging effect with an increase in the free volume of polymer chains evidenced by a decrease in the glass transition temperature (Tg) and a decrease in the tensile stiffness and yield stress. As a result, there is an abrupt increase in ductility, finding a dramatic change in the fracture behavior, from brittle to ductile. The use of digital image correlation (DIC) of the strain field analysis during fracture testing has allowed relating the decrease on the yield stress promoted by quenching with the crack propagation kinetics. The use of the EWF method to characterize the fracture toughness of PLA has allowed to measure this enhancement on toughness, finding that the specific essential work of fracture (we) and the plastic term (βwp) parameters increased 120% and 1200%, respectively, after the quenching process.